Effects of family history and sex on diabetes-related outcome in type 2 diabetes - Analysis from the tyrolean diabetes registry. - Clemens Plattner; Bernhard Pfeifer; Harald Sourij; David Vill; Marietta Wiedl; Klaus Middeldorf; Egon Eisendle; Robert Eiter; Christian Ciardi; Karin Pölzl; Julia Schock; Di Chen-König; et al. (PLoS ONE)
Aims Family history for diabetes (FHD) is a strong risk factor for type 2 diabetes (T2D), however, little is known on its effects on the outcome. Here we aimed to analyse the effects of FHD on diabetes-related outcome. Methods 7866 patients with T2D from the Tyrolean Diabetes Registry were grouped according to their FHD status. Propensity score matching for sex, BMI, HbA1c and diabetes duration provided 1440 patients per group. Survival curves were estimated using the Kaplan-Meier plot and compared using the Log-rank test. Results Mean age at T2D diagnosis was significantly lower in the FHD group, while time to insulin initiation was independent from FHD status. FHD was associated with increased risk for neuropathy (HR 1.41 [95%CI 1.11-1.81]) but decreased risk for macrovascular disease (HR 0.84 [95%CI 0.71-0.99]). Risk for total macrovascular disease, myocardial infarction, coronary artery bypass surgery and peripheral artery disease was increased by 73-156% in males in matched groups. Conclusion Family history for diabetes is not only associated with earlier diagnosis of type 2 diabetes but also affects diabetes-related outcomes with males being more prone to cardiovascular disease and patients with FHD to increased risk for neuropathy but decreased risk for macrovascular disease.